2020
DOI: 10.1002/lno.11426
|View full text |Cite
|
Sign up to set email alerts
|

Land use drives nitrous oxide dynamics in estuaries on regional and global scales

Abstract: Urban and agricultural development of coastal catchments is known to increase dissolved nitrogen inputs into estuaries; however, much less is known about how land use influences the production of the powerful greenhouse gas nitrous oxide (N 2 O). Here, we assess dissolved N 2 O dynamics in four nearby estuaries across a regional land use gradient and summarize the literature to put the observations into global perspective. During summer dry conditions, N 2 O saturation ranged from 131.4% AE 45.0% in the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
1
25
2
Order By: Relevance
“…A recent study demonstrated that CH 4 production by cyanobacteria is linked to general cell metabolism and does not rely on the presence of methylated precursor compounds (Bižić et al, 2020). Deep within the ocean's pelagic interior, CH 4 is weakly undersaturated, reflecting depletion via microbial oxidation (Reeburgh, 2007;Weber et al, 2019). Towards the coastline, CH 4 supersaturation increases by orders of magnitude ( Fig.…”
Section: Methane In Marine Environmentsmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study demonstrated that CH 4 production by cyanobacteria is linked to general cell metabolism and does not rely on the presence of methylated precursor compounds (Bižić et al, 2020). Deep within the ocean's pelagic interior, CH 4 is weakly undersaturated, reflecting depletion via microbial oxidation (Reeburgh, 2007;Weber et al, 2019). Towards the coastline, CH 4 supersaturation increases by orders of magnitude ( Fig.…”
Section: Methane In Marine Environmentsmentioning
confidence: 97%
“…For the coastal and open ocean, the dominant driver of gas exchange is wind speed (e.g., Nightingale et al, 2000;Wanninkhof, 2014) whereas in nearshore, shallow water environments the interaction of water, depth, and tidal current speeds may be a major contributor to near-surface turbulence. Several k w parameterizations are now in use for coastal waters (e.g., Raymond and Cole, 2001;Kremer et al, 2003;Zappa et al, 2003;Borges and Abril, 2011;Ho et al 2011;Rosentreter et al, 2017;Jeffrey et al, 2018), which increases the uncertainties associated with CH 4 and N 2 O emissions. For example, a 5-fold variation in CH 4 emissions from a single system occurred when applying different parameterizations to the measured gradients in CH 4 (Ferrón et al, 2007).…”
Section: Ch 4 and N 2 O In Shallow Marine Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data are important because for example, the magnitude of CH 4 and N O fluxes vary over a diel period depending on the redox environment as a result of tidal effects and changes in inorganic N and O 2 availability (Seitzinger and Kroeze, 1998;Call et al, 2015;Vieillard and Fulweiler, 2014;Maher et al, 2015;Murray et al, 2015;Foster and Fulweiler, 2019). The magnitude of CH 4 and N 2 O fluxes also varies over longer temporal scales (seasonally to yearly) due to additional factors such as groundwater inputs, adjacent land-use, dissolved O 2 , organic matter content and quality, and macrofaunal distributions (Barnes and Upstill-Goddard, 2011; Upstill-Goddard and Barnes, 2016;Gelesh et al, 2016;Bonaglia et al, 2017;Borges et al, 2018;Wells et al, 2018;Ray et al, 2019;Al-Haj and Fulweiler, 2020;Reading et al, 2020). To determine the contributing factors and resolve the spatial distributions, mobile sampling platforms such as small vessels (Müller et al, 2016;Brase et al, 2017;Tait et al, 2017), and autonomous vehicles (Manning et al, 2019) are essential.…”
Section: Ch 4 and N 2 O In Shallow Marine Environmentsmentioning
confidence: 99%
“…Estuaries contribute between 1 and 7 Tg of CH 4 and 0.1 to 0.25 Gt of CO 2 to the atmosphere each year [9], with the global flux of CO 2 to the atmosphere from estuaries comparable to the uptake of the entire continental shelf, despite estuaries representing only 5% of the continental shelf equivalent surface area [10]. Increasing inputs of anthropogenic pollutants stemming from urban, industrial and agricultural runoff into adjacent estuarine ecosystems have been reported to elevate GHG fluxes [11][12][13]. CH 4 emissions originating from microbial sources have been suggested to contribute about 70% of all global methane emissions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%